2017
DOI: 10.1103/physrevb.96.144436
|View full text |Cite
|
Sign up to set email alerts
|

Magnon-phonon coupling effects on the indirect K -edge resonant inelastic x-ray scattering spectrum of a two-dimensional Heisenberg antiferromagnet

Abstract: We compute the effects of magnon-phonon coupling on the indirect K-edge bimagnon resonant inelastic x-ray scattering (RIXS) intensity spectrum of a square lattice Heisenberg antiferromagnet. We analyze the effects of competing nearest and next-nearest magnetic and magnon-phonon coupling interaction in the RIXS spectrum, for both the antiferromagnetic (AF) and the collinear antiferromagnetic (CAF) phases of the model. Utilizing the Dyson-Maleev representation of spin operators, the Bethe-Salpeter ladder approxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
(121 reference statements)
1
4
0
Order By: Relevance
“…[51], section IV). Similar to the recent calculations on the effect of one-phonon-two-magnon to the indirect K-edge resonant inelastic x-ray scattering spectrum of a 2D Heisenberg antiferromagnet [61], we find that spin waves in 1D chain are also affected by the lattice distortion. In particular, the periodic lattice distortion affect spin waves, which in turn leads to the phonon softening at small q similar to our observation in NaFeAs (Fig.…”
Section: Theoretical Considerations and Density Functional Theory Calsupporting
confidence: 89%
See 1 more Smart Citation
“…[51], section IV). Similar to the recent calculations on the effect of one-phonon-two-magnon to the indirect K-edge resonant inelastic x-ray scattering spectrum of a 2D Heisenberg antiferromagnet [61], we find that spin waves in 1D chain are also affected by the lattice distortion. In particular, the periodic lattice distortion affect spin waves, which in turn leads to the phonon softening at small q similar to our observation in NaFeAs (Fig.…”
Section: Theoretical Considerations and Density Functional Theory Calsupporting
confidence: 89%
“…Although such mechanism is no different from the usual magnetoelastic coupling or magnon-phonon coupling, it provides a simple pictorial way to visualize such coupling. Theoretically, it has been found that spin-lattice coupling due to the one-phonon-two-magnon scattering process in an antiferromagnet can affect the spin wave broadening/damping, dispersion, and intensity [61]. Since spin fluctuations in iron pnictides exhibit spin-wave-like features above T N up to very high temperatures [62], such magnon-phonon coupling must also exist in the paramagnetic tetragonal phase.…”
Section: Theoretical Considerations and Density Functional Theory Cal...mentioning
confidence: 99%
“…Experimental [30][31][32][33][34][35][36][37] , theoretical [38][39][40][41][42][43][44][45][46] , and computational [47][48][49][50] investigations have demonstrated that resonant inelastic x-ray scattering (RIXS) spectroscopy can provide a rich source of physics information. Theoretical studies detailing the effects of magnetic frustration 51 , triangular lattice geometry 52 , magnon-phonon coupling 53 , and multi-band excitation 54 of the bimagnon excitation at the K -edge indirect RIXS have been reported. Motivated by the conceptual underpinnings of the aforementioned RIXS studies and the occurence of the chiral 245 class of chalcogenides we investigate the following question -"Can indirect K -edge RIXS spectrosocpy assist with the detection of lattice chirality?"…”
Section: Introductionmentioning
confidence: 99%
“…The magnon dynamics under the effect of magnetoelastic coupling has attracted a high interest Masciocchi et al (2022), Chen et al (2023), Luo et al (2023), Gries et al (2022), Cong et al (2022), Challali et al (2023), Sun et al (2022), Holanda et al (2018, Xiong et al (2017), Li et al (2020, Hayashi & Ando (2018), Weiler et al (2012), Zhang et al (2019Zhang et al ( , 2020, Sasaki et al (2021), Mingran et al (2020), Morais et al (2021), Sales et al (2018Sales et al ( , 2023. In Chen et al (2023), the authors investigate the magnon propagation using a Boltzmann method framework which includes magnon-phonon interaction and diverse scattering terms.…”
Section: Introductionmentioning
confidence: 99%